2017
DOI: 10.3233/bmr-150477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of lidocaine and betamethasone dipropionate in carpal tunnel syndrome injection

Abstract: Considering the potential side effects of corticosteroid, lidocaine injection is a good alternative treatment of carpal tunnel syndrome instead of corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Several RCTs have compared corticosteroid injection with either placebo injection (saline or local anesthetic) or with no treatment [34,[38][39][40][41][42][43][44]. Pooling data from three trials at short term (2 to 4 weeks) showed that the probability of improvement was 0.71 with corticosteroid and 0.31 with placebo corresponding with a relative risk of 2.2 (95% CI 1.6 to 3; 3 studies; 210 participants) [39,40,43].…”
Section: Do Corticosteroid Injections Work?mentioning
confidence: 99%
“…Several RCTs have compared corticosteroid injection with either placebo injection (saline or local anesthetic) or with no treatment [34,[38][39][40][41][42][43][44]. Pooling data from three trials at short term (2 to 4 weeks) showed that the probability of improvement was 0.71 with corticosteroid and 0.31 with placebo corresponding with a relative risk of 2.2 (95% CI 1.6 to 3; 3 studies; 210 participants) [39,40,43].…”
Section: Do Corticosteroid Injections Work?mentioning
confidence: 99%
“…Subsequently, 121 studies were excluded, and 5 studies were added through searching for references. In all, 18 RCTs met the inclusion criteria ( Peters-Veluthamaningal et al, 2010 ; Ginanneschi et al, 2012 ; Karadaş et al, 2012 ; Atroshi et al, 2013 ; Bahrami et al, 2015 ; Wu et al, 2017c ; Dernek et al, 2017 ; Uzun et al, 2017 ; Raeissadat et al, 2018 ; Wu et al, 2018 ; Güven et al, 2019 ; Senna et al, 2019 ; Shen et al, 2019 ; Boonhong and Thienkul, 2020b ; Hsu et al, 2020 ; Chen et al, 2021 ; Forogh et al, 2021 ). We extracted the outcomes (changes in the visual analog scale, symptom severity scale, and functional status scale) for further data analysis in a short-term (before or near 12 weeks) follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there are no prior studies comparing different corticosteroid doses in combination with hydrodissection in elderly patients. Dernek et al 45 studied 67 CTS patients diagnosed on the basis of physical examination and NCSs. Some received a blend of 0.5 mL normal saline solution and 0.5 mL lidocaine, while the rest received 1 mL betamethasone dipropionate.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the authors suggested lidocaine injection was an excellent alternative to corticosteroid injection, without potential side effects. 45 Another randomized, placebo-controlled trial by Karadas et al in CTS patients was conducted in 2012. They enrolled 57 CTS patients, who were assigned to one of three groups: group 1 received 1 mL 0.09% normal saline, group 2 received 40 mg triamcinolone acetonide, and group 3 received 4 mL 1% procaine HCl.…”
Section: Discussionmentioning
confidence: 99%